A College-School Cooperative Secondary Science Teacher Education Program. - Berger, J. Joel; Goldberg, Harris P. (Science Education)
The article discusses the college-school cooperative secondary science teacher education program for the faculty of Richmond College of the City University of New York in New York City. The cooperative program aims to become a way by which college science educators could effect changes in attitude among classroom science teachers. To initiate a change in the role of the college supervisor with regards to the classroom teacher is the second goal of program. A weekly after-school seminar is an important feature of the program. Issues and ideas involving teaching-learning process are being discussed by cooperating teachers, student teachers, and college faculty in the weekly seminars.